Provider Interdependence, Patient Complexity, and Continuity of Care. (20th August 2020) - Everett, C.; Price, A.; Butterfield, R.; Morgan, P.; Smith, V.; Docherty, S.; Matheson, E.; Anderson, J.; Viera, A.; Jackson, G.
Abstract : Research Objective: Patient continuity of care (CoC) with a primary care (PC) provider is associated with improved outcomes, particularly for medically complex patients. Given the difficulty for a single provider to deliver all services required to the patients on his/her panel, PC providers often provide care to each other's patients, or "share" common patients. This patient sharing, or interdependence, is not well described, and its impact on patient CoC is unknown. Objectives include the following: (a) To describe PC provider (PC physician, physician assistant [PA], or nurse practitioner [NP]) interdependence (the extent to which patients on a provider's panel are served by other providers within the practice) and (b) to evaluate the association of patient and panel characteristics, including PC provider interdependence, on patient CoC. Study Design: This patient‐level cohort study used electronic health record data from 26 health system‐affiliated PC practices in central North Carolina. Patients' usual PC provider was the provider most frequently seen during 2016. Patient‐level variables (demographic, medical complexity, and PC utilization variables) were used to calculate panel level variables [panel size, visit number, and provider interdependence (# shared patients / # supplemental providers)]. We examined the association of patient CoC (% of PC visits with usual PC provider) with all variables simultaneously using binomial regression with clustering by practice. Postestimation margins of CoC were calculated using delta method standard errors for a complex patient based on age, number of chronic conditions, and number of PC visits for a complex patient (80‐year‐old woman with ≥ 9 chronic conditions and 43 PC visits) and less complex patient (55‐year‐old man with two chronic conditions and four primary care visits). CoC was calculated for each patient on panels with a range of values (minimums, maximums, and/or means) for panel level variables. Population Studied: Adult patients with diabetes (N = 19 957). Principal Findings: PC patient panels (N = 164) were led by physicians (N = 134), NPs (N = 20) and PAs (N = 10). Panels for physicians were larger (mean = 131) than NP (mean = 80) or PA (mean = 80). Thirty‐nine % of patients had a visit with a supplemental provider. Panels were served by a mean of 7.6 providers (PCP + supplemental providers), with a mean interdependence of 7.3 patients/supplemental provider. Patient‐level CoC ranged from 6% to 99%. Panel characteristics affected the CoC of complex patients (6‐98%) more than less complex patients (61‐99%). CoC values of the complex patient were lowest when on small panels (6%‐27%) for all provider types. Higher interdependence reduced CoC for complex patients, but improved CoC for less complex patients. Conclusions: Patient characteristics and panel characteristics affect patient CoC. Complex, high utilizing patients are at greater risk of low CoC, particularly if they are on small panels that are served by many providers. Less complex patients experienced acceptable CoC regardless of panel characteristics. Implications for Policy or Practice: Organizations using or considering interdependent, multiple‐provider teams should pay special attention to the impact on high utilizing, complex patients. Complex patients benefit most from CoC, a measure known to be associated with improved health outcomes. Primary Funding Source: National Institutes of Health.